Australia's influenza pandemic preparedness plans: an analysis. Issue 1 (February 2018) - Itzwerth, Ralf; Moa, Aye; MacIntyre, C.
Abstract We analysed Australian plans issued by the public sector and current at the time of the last human pandemic in 2009. They came from various levels of governance, and offered guidance in key domains. Using 13 established criteria, we rated 10 plans (national, state, and territorial) for their usefulness to guide health and medical intervention, business continuity, and crisis communication, plus consideration of at-risk populations. The intended end-user of most plans was not clear, whether hospital manager, health worker, or policy maker. Scores ranged from 8 to 29 of a maximum possible of 39, with many inconsistencies between plans. Health system-related issues were better addressed than critical infrastructure and essential systems resilience. The needs of Indigenous populations and use of pneumococcal vaccination and antibiotics were rarely considered in plans. Pandemic response would be more effective if plans were standardised, clear, and were to include overlooked dimensions of a pandemic's impact as well as guidance for specified end-users.